Shifting the Paradigm in Radiation Safety - Doss, Mohan (International Hormesis Society, 2012)
The current radiation safety paradigm using the linear no-threshold (LNT) model is based on the premise that even the smallest amount of radiation may cause mutations increasing the risk of cancer. Autopsy studies have shown that the presence of cancer cells is not a decisive factor in the occurrence of clinical cancer. On the other hand, suppression of immune system more than doubles the cancer risk in organ transplant patients, indicating its key role in keeping occult cancers in check. Low dose radiation (LDR) elevates immune response, and so it may reduce rather than increase the risk of cancer. LNT model pays exclusive attention to DNA damage, which is not a decisive factor, and completely ignores immune system response, which is an important factor, and so is not scientifically justifiable. By not recognizing the importance of the immune system in cancer, and not exploring exercise intervention, the current paradigm may have missed an opportunity to reduce cancer deaths among atomic bomb survivors. Increased antioxidants from LDR may reduce aging-related non-cancer diseases since oxidative damage is implicated in these. A paradigm shift is warranted to reduce further casualties, reduce fear of LDR, and enable investigation of potential beneficial applications of LDR.